1999
DOI: 10.1002/(sici)1521-3935(19990201)200:2<460::aid-macp460>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Anionic synthesis of [1,4-poly(diene)-b-syndiotactic poly(methyl methacrylate)] diblock copolymers:7Li NMR study of the intermediate reaction of lithium poly(diene) anion with 1,1-diphenylethylene

Abstract: SUMMARY:The end-capping with 1,1-diphenylethylene (DPE) of living 1,4-poly(diene) lithiated anions prepared in cyclohexane (Chx) and toluene is a major but poorly controlled step in the synthesis of syndiotactic poly(methyl methacrylate) (sPMMA) containing block copolymers. The kinetics of the reaction have been studied by means of 7 Li NMR not only in Chx and toluene but also in their mixtures with polar solvents, since the solvent polarity must be increased for MMA to be predominantly converted into sPMMA. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…[18][19][20] The spin diffusion curve is corrected for T 1 relaxation. [7,[12][13][14][15][16][17][18][19][20][21][22][23][24] This correction is achieved by multiplying all intensities by exp. (t m /T 1 ), where T 1 is the relaxation time for the detected domain.…”
Section: General Remarkssupporting
confidence: 89%
See 1 more Smart Citation
“…[18][19][20] The spin diffusion curve is corrected for T 1 relaxation. [7,[12][13][14][15][16][17][18][19][20][21][22][23][24] This correction is achieved by multiplying all intensities by exp. (t m /T 1 ), where T 1 is the relaxation time for the detected domain.…”
Section: General Remarkssupporting
confidence: 89%
“…Experimental details are described in ref. [16] For the block copolymer IM-1 we found M n (PI) ¼ 31 000; M n (PMMA) ¼ 45 000; MWD ¼ 1.14. Block copolymer IM-2 was prepared accordingly with M n (PI) ¼ 40 500; M n (PMMA) ¼ 21 000; MWD ¼ 1.06.…”
Section: Preparation Of Materialsmentioning
confidence: 99%
“…The dramatic effect of Lewis base on the rate of addition was explained in terms of its effect on aggregation of the organolithium chain ends . In the presence of THF, these chain ends tended to disaggregate, thus improving the reactivity of anions …”
Section: Resultsmentioning
confidence: 99%
“…34 In the presence of THF, these chain ends tended to disaggregate, thus improving the reactivity of anions. 40 The coupling reaction was completed within 4-5 h. GPC monitoring in Figure 5 shows that the peaks for PS macromonomer (line a, cyan) and polyisoprenyllithium (line b, black) disappeared, while a new peak (line c, red) appeared with negligible residual precursors. This demonstrated that the coupling reaction was nearly quantitative.…”
Section: Synthesis Of Miktoarm Star Copolymer (Ps)(pi)(pchd)mentioning
confidence: 99%
“…Obviously, chemical and physical interactions among polymer groups and metal ions in SCF affect the ion transport. From this point of view, the ion transport in SCF is similar to lithium ion motion in polymer electrolyte in rechargeable lithium batteries 11–13. On the other hand, electrochemical conditions like a voltage drop in the SCF are important influencing factors on ion transport.…”
Section: Introductionmentioning
confidence: 99%